LEGAL ANALYSIS OF THE IMPLEMENTATION OF SHARI'AH INSURANCE INVESTMENT ACCORDING TO FIQH MUAMALAH - Badri Hasan; Kautsar Rizqi Safrizal; Mahmud Arfan (JURISTA: Jurnal Hukum dan Keadilan, 2024)
The principle of Sharia insurance is mutual assistance or mutual protection, where members set aside their funds as contributions related to tabarru' (charitable donations). Investments in insurance companies can be represented in the form of portfolios. A portfolio is a collection of integrated investment forms aimed at gaining investment returns. The primary objective of an investment portfolio is to achieve high returns with low risk levels to meet obligations to policyholders and for the growth of the company. Meanwhile, profitability depicts the company's ability to generate profits through all available capabilities and resources. Sharia-compliant insurance companies like Sun Life Sharia Insurance offer investment opportunities to customers through various insurance products. Each product has different contractual agreements, some requiring customers to make investments while others do not. Since Sharia-compliant insurance products containing investment elements are still relatively new, detailed explanations regarding the contracts and implementation of investments in the insurance company are necessary. The author uses a research method that includes qualitative research, which is descriptive in nature. The Fatwa of the National Sharia Council Number 21/DSN-MUI/X/2001 Regarding General Guidelines for Sharia Insurance states that Sharia insurance (ta'min, takful, or tadhamun) refers to mutual protection and assistance among individuals or parties through investments in the form of tabarru' funds that provide a return pattern to address specific risks through contracts (agreements) that comply with Sharia. Therefore, being insured is permitted in Sharia law because its fundamental principles encourage everything that strengthens the bonds among humans and alleviates their disasters, as mentioned in the Quran, Surah Al-Maidah, verse 2.